Model Evaluasi dalam Program Pendidikan - Harahap, Hasriyati; Zulqaidah; Rama Satya Tanjung; Khairul Amri Silalahi; Muhammad Iqbal (Indo-MathEdu Intellectuals Journal, 2024)
Evaluation is a systematic process for assessing program effectiveness, identifying areas that need improvement, and ensuring the achievement of established goals. Educational program evaluation models can assist in decision making to improve the quality of education and achieve set goals. This research aims to provide a comprehensive review of various evaluation models in educational programs. This research method uses a descriptive qualitative research method through a literature study method which uses data collection techniques in the form of book and journal reviews which are then analyzed and concluded from the research cited. The results of this research are to analyze the strengths and weaknesses of each model, as well as provide recommendations regarding the choice of the appropriate model according to the program context, evaluation objectives, and available resources